Preferences for Selecting a Personal Trainer by Fitness Members - Riana Br Saragih; Antonius Tri Wibowo (Universitas Riau, 2025)
A personal trainer is a professional workforce who has knowledge and expertise in the field of fitness training, where they have the task of helping their clients to achieve their ideal body targets by using various aspects and factors that they have in the form of consultation, questions and answers, training programs and patterns to motivation and training equipment that they have, The purpose of this research is to examine the preferences of selection criteria Personal trainer by Fitness Members. This study examined the preferences of personal trainer selection criteria by involving 10 active female members at WZone Gym Studio Babarsari Yogyakarta. This study uses a descriptive qualitative approach with semi-structured interviews. The results showed the order of priority preference of the Personality criteria (90%) friendly, comfortable, communicative, motivating, and ideal posture as an early indicator of trust. Experience & background (80%) Coaching history and previous members' results take precedence over degrees. Price, promos and value for money are the main triggers, especially for students and beginners, Certification (60%) is only supportive, practical skills are much more important. As the main determinant, the reference of all Wzone members should be given a reference from. These findings recommend female gym management to recruit friendly and experienced PTs, offer promo packages plus trials, and highlight visual testimonials to increase member satisfaction and retention.